Rozwiązane

Oblicz zmienną:
[tex]1. \frac{6x+2}{3} = 2\\2. -x + \frac{1}{2} = 2 + \frac{1}{2}x\\3. \frac{3}{4}x - x + 11 = 3\\4. 4x - 8 - 7x + 5 = 9[/tex]



Odpowiedź :

Magda

Odpowiedź:

[tex]1.\\\\\frac{6x+2}{3}=2\ \ /\cdot3\\\\6x+2=6\\\\6x=6-2\\\\6x=4\ \ /:6\\\\x=\frac{4}{6}\\\\x=\frac{2}{3}\\\\\\2.\\\\-x+\frac{1}{2}=2+\frac{1}{2}x\ \ /\cdot2\\\\-2x+1=4+x\\\\-2x-x=4-1\\\\-3x=3\ \ /:(-3)\\\\x=-1[/tex]

[tex]3.\\\\\frac{3}{4}x-x+11=3\\\\-\frac{1}{4}x=3-11\\\\-\frac{1}{4}x=-8\ \ /\cdot4\\\\-x=-32\ \ /\cdot(-1)\\\\x=32\\\\\\4.\\\\4x-8-7x+5=9\\\\-3x-3=9\\\\-3x=9+3\\\\-3x=12\ \ /:(-3)\\\\x=-4[/tex]